Oxidative stress induced in E. coli by the human antimicrobial peptide LL-37. - Heejun Choi; Zhilin Yang; James C Weisshaar (PLoS Pathogens, 2017)
Antimicrobial peptides (AMPs) are thought to kill bacterial cells by permeabilizing their membranes. However, some antimicrobial peptides inhibit E. coli growth more efficiently in aerobic than in anaerobic conditions. In the attack of the human cathelicidin LL-37 on E. coli, real-time, single-cell fluorescence imaging reveals the timing of membrane permeabilization and the onset of oxidative stress. For cells growing aerobically, a CellROX Green assay indicates that LL-37 induces rapid formation of oxidative species after entry into the periplasm, but before permeabilization of the cytoplasmic membrane (CM). A cytoplasmic Amplex Red assay signals a subsequent burst of oxidative species, most likely hydrogen peroxide, shortly after permeabilization of the CM. These signals are much stronger in the presence of oxygen, a functional electron transport chain, and a large proton motive force (PMF). They are much weaker in cells growing anaerobically, by either fermentation or anaerobic respiration. In aerobic growth, the oxidative signals are attenuated in a cytochrome oxidase-bd deletion mutant, but not in a -bo3 deletion mutant, suggesting a specific effect of LL-37 on the electron transport chain. The AMPs melittin and LL-37 induce strong oxidative signals and exhibit O2-sensitive MICs, while the AMPs indolicidin and cecropin A do not. These results suggest that AMP activity in different tissues may be tuned according to the local oxygen level. This may be significant for control of opportunistic pathogens while enabling growth of commensal bacteria.